National Policy for Regional Development: Historical Evidence from Appalachian Highways - Jaworski, Taylor; Kitchens, Carl T. (The Review of Economics and Statistics, 2019)
How effective are policies aimed at integrating isolated regions? We answer this question in the context of a highway system in one of the poorest regions in the United States. With construction starting in 1965, the Appalachian Development Highway System (ADHS) ultimately consisted of over 2,500 high-grade road miles. We use a simple model of interregional trade to motivate our empirical analysis, which quantifies the relationship between market access and income. We then calibrate the model to evaluate the aggregate impact of the ADHS and compare this with alternative counterfactual proposals. We find that removing the ADHS would have reduced total income by $53.7 billion in the United States, with $22 billion of the losses in Appalachian counties. Our findings highlight the potential aggregate benefits of transportation infrastructure policies and suggest that leakage outside the targeted area may be substantial.